EFFECTIVENESS OF DIGITAL EDUCATIONAL TECHNOLOGIES IN TEACHING OFTALMOLOGY BASED ON PROBLEM CASES - Oripov O. I.; Dekhkambaeva Z. A.; Dursunov S. A.; Tagaev G. P. (Modern American Journals, 2025)
This article provides a theoretical analysis of the effectiveness of using the case-based learning (CBL) approach and digital educational technologies in teaching ophthalmology. Modern medical education requires students to develop clinical reasoning, independent decision-making, and adaptability to real clinical scenarios. In particular, integrating digital tools such as virtual simulators, online cases, instructional videos, and distance learning platforms with traditional classroom instruction is becoming increasingly important in ophthalmology education. Based on a review of scientific literature and current practice, the article substantiates that the synergy of case-based learning and digital technologies enhances the quality and effectiveness of ophthalmology teaching. It also highlights the positive impact of these methods on students' academic performance, motivation, and acquisition of practical skills.
Keywords: Ophthalmology, case-based learning, digital education, distance learning, virtual simulation, clinical reasoning.